Business Model Canvas for Kenaf Fiber Agro-industry Development inUpstream Supply Chain Networks - Nurhasanah, Nunung Nurhasanah; Hakim, Muhammad Hakim; Chirzun, Ahmad Chirzun; Sriwana, Iphov; Ramadanti, Amelia (JURNAL TEKNIK INDUSTRI, 2024)
Kenaf fiber is one of plant-based fibers used as an industrial raw material. The business model canvasin this study was an approach used to describe the business model of kenaf fiber agro-industry in theupstream supply chain network. This study aimed to identify value propositions, structural models ofdevelopment strategies, and to design a business model canvas for the agro-industry. AnInterpretative structural modelling method was used to construct a structural model for thedevelopment strategy, and the business model canvas was used to describe this agro-industrybusiness model. BMC is a framework that helps business people describe the current business model.This approach is a static approach that uses past data. However, this approach becomes dynamicafter being integrated with certain scientific methods so that it is able to describe its business modelin the future. The structural model identified that the prominent element that had the significantinfluence on this business was seed suppliers, while the prominent element in development of thisagro-industry strategy was an institution. This research is still limited to the upstream supply chainnetwork, therefore, future research can be developed on the mid-stream and downstream supplychain networks.